A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Cu Lao Cham Islands, central Vietnam - Nguyen, Sang Ngoc; Nguyen, Luan Thanh; Nguyen, Vu Dang Hoang; Phan, Hoa Thi; Jiang, Ke; Murphy, Robert W. (Zootaxa, 2017)
A new kukri snake, Oligodon culaochamensis sp. nov., is described from Cu Lao Cham Islands, central Vietnam, based on the morphology of six specimens, including two males, three females and one juvenile. The new species belongs to the O. cyclurus group and differs from other congeners in this group by a combination of the following characters: medium size in adults (total length up to 582 mm); 17–19 dorsal scale rows at neck and midbody and 15 or 17 rows before vent; tail length/total length ratio 0.218–0.219 in males and 0.166–0.169 in females; ventrals 167–169 in males and 179–182 in females; subcaudals 63–66 in males and 51–52 in females; head scalation complete with a presubocular; 9–10 maxillary teeth, the posterior three being enlarged; nasal divided; temporal streak absent; long and deeply forked hemipenes extending to 20th subcaudal and without spines and papillae but with prominent diagonal ridge, oblique flounces and distal calyces; cloacal plate undivided; 10–11+3–4 dorsal blotches; and a vertebral stripe on tail and anterior part of body. This is the second species of Oligodon described on islands of Vietnam.